The future for creative writing - Harper, Graeme (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2014)
"This is a compelling look at the current state and future direction of creative writing by a preeminent scholar in the field. Explores the practice of creative writing, its place in the world, and its impact on individuals and communities Considers the process of creative writing as an art form and as a mode of communication Examines how new technology, notably the internet and cell phones, is changing the ways in which creative work is undertaken and produced Addresses such topics as writing as a cultural production, the education of a creative writer, the changing nature of communication, and different attitudes to empowerment "--
"Addresses such topics as writing as a cultural production, the education of a creative writer, the changing nature of communication"--
The Age of Creative Writing -- Dynamism and the Creative Writer -- Creative Writing Educating -- Developing Creative Exposition -- Selling and Buying Creative Writing -- Speaking in Creative Writing -- Living and Working as a Creative Writer.
Machine generated contents note: Acknowledgments vii Introduction 1 1 The Age of Creative Writing 17 2 Dynamism and the Creative Writer 35 3 Creative Writing Educating 53 4 Developing Creative Exposition 71 5 Selling and Buying Creative Writing 89 6 Speaking in Creative Writing 107 7 Living and Working as a Creative Writer 119 Conclusion 135 Selected Reading 143 Index 149 .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Creative writing; Rhetoric; EDUCATION / Teaching Methods & Materials / Reading & Phonics; Creative writing; Rhetoric; Electronic books